A longitudinal birth cohort study of child maltreatment and mental disorders using linked statewide child protection and administrative health data for 83,050 Queensland residents from 1983 to 2014 - Steve Kisely; Stuart Leske; James Ogilvie; Carleen Thompson; Dan Siskind; Troy Allard (Cambridge University Press, 2024)
Abstract Aims Most information about the association between childhood maltreatment (CM) and subsequent psychiatric morbidity is based on retrospective self-reports. Findings from longitudinal studies using prospective reports to statutory agencies may be subject to attrition. We therefore compared the prevalence to age 30 of inpatient psychiatric diagnoses in those who experienced agency-reported CM with those of the rest of the cohort using administrative data to minimise loss to follow-up. Methods We used linked administrative data for two birth cohorts of all individuals born in Queensland, Australia in 1983 and 1984 (N = 83,050) and followed to age 30 years. This was the entire cohort aside from 312 people who died. Information on CM came from statewide child protection data and psychiatric diagnoses from all public and private hospital admissions in Queensland. Results On adjusted analyses, the 4,703 participants (5.7%) who had been notified to the statewide child protection authority had three to eight times the odds of being admitted for any of the following psychiatric diagnoses by age 30 years old: schizophrenia-spectrum disorders, bipolar affective disorders, depression, anxiety and post-traumatic stress disorders (PTSD). There were similar findings for all the CM subtypes. Associations were especially strong for PTSD with between a seven - and nine-fold increase in the odds of admission. Conclusions This is one of the largest studies of the long-term effects of CM, covering an entire jurisdiction. All types of maltreatment are significantly related to a range of psychiatric disorders requiring hospitalisation. Early identification, intervention and providing appropriate support to individuals who have experienced CM may help mitigate the long-term consequences and reduce the risk of subsequent mental health problems.